AKUNTABILITAS TRANPARANSI PENDANAAN SARANA PRASARANA DALAM MANAJEMEN BERBASIS SEKOLAH DI PAUD ASHOFA ASTHILA KAMPAR - Andriani, Rita; Fadila, Rizka; Suriani, Erma; Marhadi, Hendri (FKIP Universitas Al Washliyah Medan, 2024)
Accountability and transparency in managing school funding within School-Based Management (SBM) are key principles guiding how schools manage, utilize, and report funds. This study aims to explore these practices in funding management for facilities at PAUD Ashofa Atshila. Using qualitative methods, the study involved the school principal and one administrative staff member as informants. Data were collected through observations, interviews, and documentation. The study found that SBM at PAUD Ashofa Atshila Kampar has improved facilities supporting the teaching and learning process, such as televisions, air conditioners (AC), and projectors. To enhance fund management quality, PAUD Ashofa Atshila Kampar needs to improve its understanding and practice of accountability and transparency. Necessary steps include regular financial reporting, clear communication about fund usage to all school stakeholders, and community participation. In conclusion, implementing SBM at PAUD Ashofa Atshila Kampar has increased accountability and transparency in managing funding for facilities and infrastructure. This positively impacts the enhancement of teaching facilities, making the educational process more effective. Currently, facilities at PAUD Ashofa Atshila Kampar are in the procurement stage. However, shortcomings in transparency and accountability, such as the lack of regular financial reports, need to be addressed.